Scaling for Impact: Organizational Readiness & Scaling Strategies for Nonprofits within the Circular Economy - Aynedjian, Cynthia; Karlsson, Wilma (My University, 2025)
Societal challenges, such as marine pollution, is complex and often implies uncertain financial return. In contrast to for-profits, nonprofit organizations play an important part since they focus on creating impact rather than generating financial return. Existing theory focuses on scaling operations within for-profit entities and assumes that all nonprofits want to scale. Hence, gaps exist in understanding whether all nonprofit organizations aim to scale and what scaling efforts they pursue. This study aimed to fill those gaps, by conducting a qualitative case study investigating 12 different organizations operating in marine pollution. Based on findings, this study reveals that not all nonprofits aim to scale. It is nonprofit organizations with a proactive strategic posture that will pursue scaling efforts if these align with their core mission. Additionally, organizations that are operationally flexible and financially diversified are the organizations who achieve the greatest scaling reach. Ultimately, this study contributes with two new concepts: Scaling Readiness and Scaling Performance which provides a more nuanced perspective on scaling. Scaling Readiness refers to the organization’s internal preparedness to scale, which is shaped by its strategic fit as well as the scaling conditions. Scaling Performance suggest that scaling can be done in different ways and to different degrees. Moreover, this study highlights that scaling is not a one-time event, rather it is an iterative process, especially when it is done to scale impact. These findings enhance the understanding of scaling in the context of nonprofit organizations, which is crucial since scaling is needed to match the magnitude of the societal challenge with marine pollution.
Keywords: Circular economy; marine plastic waste; nonprofit organization; scaling; scaling deep; scaling wide; resource dependency; financial sustainability